USOS E APROPRIAÇÕES DA REDE SOCIAL DIGITAL: ANÁLISE DA RELAÇÃO ENTRE LEITOR/AUTOR NA ATUALIZAÇÃO DO JORNALISMO - Rodrigues Barreto, Simone (LINKSCIENCEPLACE, 2026)
This paper aims to make some considerations about the reader’s participation, now "user" in the media glare of Social Networks Digital with online and print media, from the identification and analysis of situations where Facebook served as a source of information or reproduction of thoughts or opinions in articles published in printed newspapers and online channels. The considerations are drawn from the entries mapping to Facebook about the death of a student of Unesp, on March 1, 2015, in addition to appropriations of texts, photos and videos circulated on social networks and were published journalistically. It was observed that most of materials used as a source social network content. It is intended in this article also make reflections on the use and ownership of Facebook, analyzing the relationship between reader / user and news production in journalism as a rhizomatic process, conceptualized by Deleuze and Guattari. Based on the concept of Lévy, observe reader participation, before mere spectator, now as one of the responsible for updating the news through comments left on news sites or social networks.